Penerapan Manajemen Berbasis Sekolah di SD Negeri Satriyan 02 - Muhammad Rizka Arga; Lintang Cahyaningtyas; Elsa Safara; Mutiara Safa Kamila; Lisa Virdinarti Putra (Yayasan Literasi Sains Indonesia, 2025)
School-Based Management is an educational management approach that grants autonomy to schools to manage themselves, particularly in terms of planning, implementation, monitoring of school activities, decision-making, and resource management in order to improve the quality of education. This study aims to describe and analyze the implementation of School-Based Management (SBM) at SD Negeri Satriyan 02. The research utilizes a descriptive method with a qualitative approach. Data collection techniques include interviews with teachers at SD Negeri Satriyan 02 and a literature review of relevant sources. The information was analyzed thematically to identify patterns and meanings related to the principles of SBM implemented at the school, including stakeholder participation, decentralized decision-making, curriculum and instructional management, human and financial resource management, and school accountability. The results of this research are expected to provide a comprehensive overview of SBM implementation at SD Negeri Satriyan 02, identify the supporting and inhibiting factors for its success, and offer recommendations for strengthening SBM efforts to improve the quality of education at the school.